Recording in the digital world: complete guide to studio gear and software - Rudolph, Thomas E. (Berklee guide, 2001)
Build the perfect digital studio, no matter what your budget! Creating high-quality digital recording does not require buying the most expensive equipment, but it does require buying the right equipment and knowing how to use it. This book provides professional advice and recommendations on studio equipment, software and the latest technologies, plus practical tips for creating, editing and mastering digital recordings. Perfect for professional musicians, music educators and hobbyists who want to explore the world of digital recording.